Primary mesenchymal tumors of the colon: A report of three cases - Arzu Yaren; Serkan Değirmencioğlu; Neşe Çallı Demirkan; Atike Gökçen Demiray; Burcu Taşköylü; Gamze Gököz Doğu (Turkish Journal of Gastroenterology, 2019)
Primary mesenchymal tumors of the colon are extremely rare tumors among soft tissue sarcomas. These tumors are more aggressive and have poorer prognosis than adenocarcinoma of the colon. Here, we presented 3 cases of primary mesenchymal tumors of the colon. Their histopathological diagnoses are leiomyosarcoma, pleomorphic liposarcoma, and desmoplastic small round cell tumor, respectively. The rarity of primary mesenchymal tumors of the colon makes it difficult to approach the treatment and predict the prognosis of these rare tumors.